How Does Gramsci Travel in Latin America?: Before and After Critical International Relations Theory - Tussie, Diana Alicia (2022)
In the last 40 years, Critical International Relations Theory (CIRT) has influenced scholars in the Global North as well as the South. Latin America shows particular features. On the one hand, conceptualisation did not divorce the domestic from the international, as in dependency theory. On the other, Gramsci was widely read much before Robert W. Cox and even before International Relations was constituted as a discipline in its own right. In this context, this article aims to present possible contributions of (neo)Gramscian approaches to the understanding of Latin America as a region. It does so by establishing a dialectical relationship between a few topics that offer insights (and the theoretical reflection they provoke) and some (neo)Gramscian concepts. Hence, we want to re-read, in a dialectical vein, both CIRT and some aspects of how Gramscian thought has travelled in Latin America. We intend to analyse how such thinking is thriving, if at all, and discuss the possible relevance of rescuing Gramscian international thought to think about the region.